2011
DOI: 10.1118/1.3553556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and identification of spatial artifacts during 4D‐CT imaging

Abstract: Purpose: The purpose of this work is twofold: First, to characterize the artifacts occurring in helical 4D-CT imaging; second, to propose a method that can automatically identify the artifacts in 4D-CT images. The authors have designed a process that can automatically identify the artifacts in 4D-CT images, which may be invaluable in quantifying the quality of 4D-CT images and reducing the artifacts from the reconstructed images on a large dataset. Methods: Given two adjacent stacks obtained from the same resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…26) and are a source of variability in our analysis, with the exception of subject H-12, the images in this study were examined and found to contain minimal spatial reconstruction artifacts. 27 The reconstruction artifacts may have been reduced by the audiocoaching for patient respiration and by the ability of helical mode image acquisition to allow manual selection of projection data to be used for image reconstruction at each phase. Subject H-12 had moderate motion artifacts, but it was decided to not eliminate this case from analysis.…”
Section: Iic1 Preprocessingmentioning
confidence: 99%
“…26) and are a source of variability in our analysis, with the exception of subject H-12, the images in this study were examined and found to contain minimal spatial reconstruction artifacts. 27 The reconstruction artifacts may have been reduced by the audiocoaching for patient respiration and by the ability of helical mode image acquisition to allow manual selection of projection data to be used for image reconstruction at each phase. Subject H-12 had moderate motion artifacts, but it was decided to not eliminate this case from analysis.…”
Section: Iic1 Preprocessingmentioning
confidence: 99%
“…In conventional approaches, derived from 4D CT, images are sorted retrospectively using an external surrogate . The latter may not correlate well with the actual internal motion and the limited accuracy in breathing state identification may result in artifacts …”
Section: Introductionmentioning
confidence: 99%
“…Thus, 4D-CT is often contaminated by motion artifacts which include motion blur, overlap and gapping. [27][28][29] Although the motion-related artifacts could be reduced by the breath training, 30,31 improved sorting method, 1,29,32,33 utilization of internal anatomical features, 25,34,35 and postimage processing on 4D-CT images, 16,36,37 the interslice thickness (e.g., 3 mm), which is often much higher than the intraslice resolution (e.g., 1 mm), still remains as a big challenge in 4D-CT registration. Often, vessels become discontinuous across neighboring slices, which makes it difficult to perform reasonable registration especially for small vessels.…”
Section: Ib Related Workmentioning
confidence: 99%